A comparative estimation of quercetin content from Cuscuta reflexa Roxb.using validated HPTLC and HPLC techniques - Sunita Shailajan, Harshvardhan Joshi, Bhavesh Tiwari (Journal of Applied Pharmaceutical Science, 2014)
HPTLC and HPLC are two most widely accepted methods for determination of natural products. Present research work envisages microwave assisted extraction of quercetin from hydroethanolic extract of Cuscuta reflexa Roxb. (Cuscutaceae), an unusual parasitic vine. Further, chromatographic characterization of hydroethanolic extract of C. reflexa was carried out in terms of quercetin content using two validated methods (HPTLC and RP-HPLC). Confirmation of the presence of quercetin in the samples was carried out using Mass Spectrometry. HPTLC separation of quercetin was achieved on an aluminum-backed layer of silica gel 60 F254 using Toluene: ethyl acetate and formic acid as mobile phase while RP-HPLC was performed on Cosmosil C18-column (150 mm x 4.6 mm, 5 μm) using mobile phase comprising of 0.025 M NaH2PO4 buffer – ACN (pH - 2.6) at a flow rate of 1.2 mL/min. ICH guidelines were followed for validation of both the the chromatographic methods. Samples of C. reflexa collected from different regions of India and growing on different hosts were also screened for their quercetin content. The developed chromatographic methods described here were found to be simple, rapid, accurate and sensitive.
Keywords: HPTLC, RP-HPLC, Cuscuta reflexa, quercetin, validation, regional variation.